PENGARUH KREDIBILITAS TASYA FARASYA TERHADAP NIAT BELI PRODUK FOCALLURE - Dwiartha Cahyani, Ni Made Pramoni; Alit Suryawati, I Gusti Agung; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
A person's credibility affects the communicant to make a product decision. The use of beauty vloggers is easier to influence consumers' psychology because they are individuals who are popular with society. One of the well-known beauty vloggers in Indonesia and has the highest number of subscribers is named Tasya Farasya. Tasya Farasya collaborated with Focallure in creating products by releasing the eyeshadow pallete